2018
DOI: 10.1111/1758-5899.12589
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Basic Science in an Intergovernmental Framework: Learning from CERN's Science Diplomacy

Abstract: CERN offers a highly relevant case to probe some of the assumptions of current debates on science diplomacy. Building on the existing literature and a number of expert interviews, this article discusses the origin of CERN, its governance structure, and the particular constellation of interests that form part of CERN's science diplomacy. We understand science diplomacy as a practice and explore this at the intersection between goals and values, everyday conduct, and the governance structure guiding interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…See also, for example, Moedas (2016); Ruffini (2017). CERN has, in fact, been described in recent years as a model of science diplomacy; see Höne & Kurbalija (2018), as well as the UNESCO 2015 workshop The CERN Model, United Nations and Global Public Goods: Addressing Global Challenges (UNESCO, n.d.). 12 For the notion of "imagined past" in the sciences, see Wilson (2017).…”
Section: Navigational Tools For a History Of Science Diplomacymentioning
confidence: 99%
“…See also, for example, Moedas (2016); Ruffini (2017). CERN has, in fact, been described in recent years as a model of science diplomacy; see Höne & Kurbalija (2018), as well as the UNESCO 2015 workshop The CERN Model, United Nations and Global Public Goods: Addressing Global Challenges (UNESCO, n.d.). 12 For the notion of "imagined past" in the sciences, see Wilson (2017).…”
Section: Navigational Tools For a History Of Science Diplomacymentioning
confidence: 99%
“…Science in diplomacy as evidence for global policy actors. For example, the knowledge generated by epistemic communities such as the cetologists in the development of the International Whaling Commission (Haas, 2015: 17) (Höne and Kurbalija, 2018). Of special note is the European Commission's research agenda on Science and Cultural Diplomacy promoted through the Horizon 2020 grant scheme with funding for three separate KNETs on the topic (European Commission, 2014).…”
Section: International Organisations and Transnational Policy Communitiesmentioning
confidence: 99%
“…Building the transnational capacities of government agencies suggests bureaucratic reform as well as resourcing new directions in civil service training around TGN policy concerns. Training of this type is 'heavily underexplored from the point of view of professional education outside' of the diplomatic service (Kaltofen and Acuto, 2018: 13;Jones, 2019;Höne and Kurbalija, 2018).…”
Section: International Organisations and Transnational Policy Communitiesmentioning
confidence: 99%
“…There are also tens of border and cross-border regions, connecting close (Norway-Sweden), or not-so close (Sicily-Malta), neighbours; sometimes reaching beyond the EU (Finland-Russia). And some organizations have a clear research focus, such as those in the European research infrastructure and the CERN institute in Switzerland, where the EU is one of the partners (Höne & Kurbalija, 2018).…”
Section: Functionality and Regionalismmentioning
confidence: 99%
“…Multi-level governance does not confront the sovereignty of states directly … states in the European Union are being melded gently into a multi-level polity. 'Gentle melding' may sound nice and cosy, yet subsequent research on multi-level governance found that jurisdictional overlaps can also lead to continuous negotiations, if not outright struggles and fighting, between different powers (Höne & Kurbalija, 2018). Regional initiatives are also not only functional and regional, they are also political initiatives with which powerful actors try to gain influence (Arter, 2000).…”
Section: Functionality and Regionalismmentioning
confidence: 99%